Jenis Avertebrata Air Yang Diperdagangkan Di Pasar Higenis, Kota Pangkal Pinang - Kurniawan, Ardiansyah; Dwijaya, Akbar L.; Saffa, Gelfira K.; Lestari, Indah; Pratama, Rizky A.; Azzahra, Miftahul J.; Saputra, Saputra; Saputra, Muhammad A.; Aini, Nayla Q.; Savira, Azzhara F.; Djunaidi, Brizhain A.; Khasanah, Utswatun; Ghaisan, Muhammad A.; Nafisyah, Annisa; Utami, Riski; Nuraini, Syifa; Fadillah, Muhammad Fajar; Adittia, Adittia (CV. SINAR HOWUHOWU, 2025)
This study aims to identify the types of aquatic invertebrates traded at the Hygienic Market (Pasar Higienis) in Pangkalpinang City. Data were collected through direct observation and photographic documentation of aquatic invertebrate commodities sold by traders. Species identification was conducted based on morphological characteristics, referring to relevant scientific literature. The results showed that the aquatic invertebrates traded at the Hygienic Market of Pangkalpinang City included fresh and salted squid (Loligo sp.), blood cockles (Anadara spp.), whiteleg shrimp (Litopenaeus vannamei), sea shrimp (Penaeus merguiensis), dried shrimp (ebi), tiny shrimp (rebon), mud crabs (Scylla serrata), blue swimming crab (Portunus pelagicus), and gonggong snail (Strombus turturella). The trade of aquatic invertebrates in the traditional market is dominated by high-value commodities that play an important role in fulfilling `the food needs of the local community.